Energy, Efficiency Gains and Economic Development : When Will Global Energy Demand Saturate? - Bogmans, Christian (IMF Working Papers; Working Paper, 2020)
Not anytime soon. Using a novel dataset covering 127 countries and spanning two centuries, we find evidence for an energy Kuznets curve, with an initial decline of energy demand at low levels of per capita income followed by stages of acceleration and then saturation at high-income levels. Historical trends in energy efficiency have reduced energy demand, globally, by about 1.2 percent per year and have, thus, helped bring forward a plateau in energy demand for high income countries. At middle incomes energy and income move in lockstep. The decline in the manufacturing share of value added, globally, accounted for about 0.2 percentage points of the energy efficiency gains. At the country level, the decline (rise) of the manufacturing sector has reduced (increased) US (China) energy demand by 4.1 (10.7) percent between 1990 and 2017.